Large‐sample‐size assessment of socioeconomic predictors of community‐level resource management occurrence. Issue 2 (3rd August 2021) - Brewer, Tom David; Andrew, Neil; Gruber, Bernd; Kool, Johnathan
Abstract: Community‐level resource management efforts are cornerstones in ensuring sustainable use of natural resources. Yet, understanding how community characteristics influence management practices remains contested. With a sample size of ≥725 communities, we assessed the effects of key community (i.e., socioeconomic) characteristics (human population size and density, market integration, and modernization) on the probability of occurrence of fisheries management practices, including gear, species, and spatial restrictions. The study was based in Solomon Islands, a Pacific Island country with a population that is highly dependent on coastal fisheries. People primarily dwell in small communities adjacent to the coastline dispersed across 6 island provinces and numerous smaller islands. We used nationally collected data in binomial logistic regression models to examine the likelihood of management occurrence, given socioeconomic context of communities. In contrast to prevailing views, we identified a positive and statistically significant association between both human population size and market integration and all 3 management practices. Human population density, however, had a statistically significant negative association and modernization a varied and limited association with occurrence of all management practices. Our method offers a way to remotely predict the occurrence of resource management practices based on key socioeconomic characteristics. It could be used to improve understanding of why some communities conduct natural resource management activities when statistical patterns suggest they are not likely to and thus improve understanding of how some communities of people beat the odds despite limited market access and high population density. Resumen: Los esfuerzos por manejar los recursos a nivel comunitario son pilares para garantizar el uso sustentable de los recursos naturales. Aun así, el conocimiento sobre cómo las características comunitarias influyen sobre las prácticas de manejo todavía está en discusión. Con un tamaño de muestra de ≥725 comunidades, evaluamos los efectos de las características (tamaño y densidad poblacional humana, integración del mercado y modernización) comunitarias (es decir, socioeconómicas) clave sobre la probabilidad de incidencia de las prácticas de manejo de las pesquerías, incluyendo el equipamiento, las especies y las restricciones espaciales. El estudio se ubicó en las Islas Salomón, un país isleño del Pacífico con una población altamente dependiente de las pesquerías costeras. En este país, las personas habitan principalmente en comunidades pequeñas adyacentes a la costa y dispersas en las seis provincias isleñas y en numerosas islas más pequeñas. Usamos datos recolectados en todo el país en unos modelos de regresión logística binomial para examinar la probabilidad de incidencia del manejo, dado el contexto socioeconómico de las comunidades. Contrario a las opiniones predominantes, identificamos una asociación positiva y estadísticamente significativa entre el tamaño poblacional humano y la integración del mercado y entre las tres prácticas de manejo. La densidad poblacional humana, sin embargo, tuvo una asociación negativa estadísticamente significativa y la modernización una asociación variada y limitada con la incidencia de las prácticas de manejo. Nuestro método ofrece una manera para predecir remotamente la incidencia de las prácticas de manejo de recursos con base en características socioeconómicas importantes. El método podría utilizarse para incrementar el conocimiento sobre cómo algunas comunidades llevan a cabo actividades de manejo de recursos naturales cuando los patrones estadísticos sugieren lo contrario y así mejorar el entendimiento de cómo algunas comunidades humanas superan todos los pronósticos a pesar del acceso limitado al mercado y la alta densidad poblacional. Evaluación de Muestras de Gran Tamaño de Pronosticadores Socioeconómicos de la Incidencia del Manejo de Recursos a Nivel Comunitario 【摘要】: 社区水平的资源管理工作是确保自然资源可持续利用的基础。然而, 人们对于社区特征如何影响管理实践的认识尚存有争议。本研究利用超过725个社区的样本, 评估了关键社区特征 (即社会经济特征, 包括人口规模与密度、市场一体化水平、现代化水平) 对渔业管理实践 (包括对渔具、物种及空间的限制) 发生概率的影响。我们的研究地点位于所罗门群岛, 这是一个居民高度依赖沿海渔业的太平洋岛国。该地区的人口主要分散在 6个岛屿省及许多较小岛屿上邻近海岸线的小型社区中。我们利用全国数据, 构建了特定社区社会经济背景下的二项式逻辑回归模型, 以检验管理实践的发生概率。不同于主流观点, 我们发现人口规模和市场一体化水平与所有三种管理实践之间均存在统计上显著的正相关关系。然而, 人口密度与管理实践具有统计上显著的负相关关系, 而现代化与三种管理实践之间则存在不一致且有限的相关性。我们的研究方法可作为一种基于关键社会经济特征远程预测资源管理实践发生概率的工具, 有助于更好地理解为什么一些社区会在统计模型表明其不太可能开展自然资源管理活动时仍采取管理实践, 从而深入理解一些社区的人们如何在进入市场的机会有限且人口密度高的情况下战胜不利条件。【翻译:胡怡思; 审校:聂永刚】